Root-dentin sensitivity following non-surgical periodontal treatment - Tammaro, Stefano; Wennström, Jan L.; Bergenholtz, Gunnar (Journal of clinical periodontology, 2000)
Background, aims: Little clinical data exist on the incidence and severity by which root dentin sensitivity (RDS) results from periodontal therapy. The aim of the present clinical trial was to study the degree to which a sample of patients requiring non‐surgical periodontal treatment develops RDS. Material and methods: Alterations in RDS was followed in 35 patients (29–65 years of age) requiring non‐surgical treatment for moderate to advanced periodontal disease. Inclusion criteria for participation were need for periodontal treatment in at least 2 quadrants comprising a minimum of 4 teeth with vital pulps, no open caries lesions, no dental treatment in the last 3 months and no ongoing treatment for RDS. Baseline and follow‐up recordings included responses of teeth to pain stimuli (directed compressed air) at buccal surfaces as graded by the patient on a 10‐cm visual analogue scale (VAS). Periodontal therapy consisted of oral hygiene instruction (OH) followed by supra‐ and subgingival scaling/root planing by hand and ultrasonic instrumentation of one quadrant per each of the subsequent weeks. Thus, follow‐up data included pain assessment after 1–3 weeks of OH alone, and 1–4 weeks post‐instrumentation. Results: There was a statistically significant reduction in mean VAS‐scoring over time in quadrants where only meticulous plaque control had been maintained, while VAS mean values increased significantly after instrumentation (p<0.001). Also the % of subjects reporting higher mean VAS values increased after instrumentation. Changes in mean VAS scores were generally moderate and only 9 patients gave an increase on VAS of >2 cm for 3 or more teeth. A statistically significantly higher increase of RDS was observed for initially sensitive teeth (VAS>0) than for teeth not responding at baseline (p<0.001). Although a reduction in the intensity of RDS could be noticed during the later phase of the 4‐week follow‐up period after scaling and root planing, the percentage of sensitive teeth remained unchanged. Conclusion: The data confirm that meticulous plaque control will diminish RDS problems and that scaling and root planing procedures in periodontal therapy result in an increase of teeth that respond to painful stimuli. However, pain experiences in general appeared minor and only a few teeth in a few patients developed highly sensitive root surfaces following instrumentation.